(untitled) (Management and Connections Journal, 2013)
DOI: http://dx.doi.org/10.13071/regec.2317-5087.2013.2.2.6137.181-206 This is a study of the science and technology policy of the government of São Paulo in the First Republic (1890-1930). This policy led to the creation of major research institutions and various higher education institutions in the State of São Paulo. The cornerstone of this paper is to identify and characterize the economic, social and cultural conditions that allowed the genesis and evolution of this policy shall, evaluating its main effects in the medium and long term.